Contribution of the Ansor Youth Movement in the Indonesian National Movement in 1934-1950 - Hartono; Subekti, Arif (Journal of Islamic Civilization, 2022)
As an NU wing organisation, GP Ansor was born with various dynamics of its long journey. The birth of GP Ansor was inspired by the spirit of nationalism to achieve Indonesian independence. GP Ansor was born with two main missions, namely religious and national missions. This article aims to examine the history of the birth of GP Ansor and his various contributions in the journey of the Indonesian nation. The method used in this research is the historical research method. This method consists of, Heuristics, Source Criticism, Interpretation and Historiography. The sources used in this research are scientific articles, archives, documents, books, newspapers, thesis and other relevant sources. These sources are analysed and studied in depth to obtain a clearer picture. The results of this study concluded that GP Ansor is an organisation that has a major contribution to the Indonesian national movement. GP Ansor made various efforts to win and defend Indonesia's independence.  These efforts were carried out intensively, consistently and continuously as a tangible proof of GP Ansor's contribution in fulfilling his national mission. Sebagai organisasi sayap NU, GP Ansor lahir dengan berbagai dinamika perjalanannya yang panjang. Kelahiran GP Ansor diilhami oleh semangat nasionalisme untuk meraih kemerdekaan Indonesia. GP Ansor lahir dengan mengemban dua misi utama yakni misi keagamaan dan kebangsaan. Artikel ini bertujuan untuk menelisik sejarah kelahiran GP Ansor dan berbagai kontribusinya dalam perjalanan bangsa Indonesia. Metode yang digunakan dalam penelitian ini adalah metode penelitian sejarah. Metode ini terdiri atas, Heuristik, Kritik Sumber, Intepretasi dan Historiografi. Sumber-Sumber yang digunakan dalam penelitian ini adalah artikel ilmiah, arsip, dokumen, buku, surat kabar, skripsi dan sumber-sumber lain yang relevan. Sumber-sumber tersebut dianalisi dan dikaji secara mendalam untuk memperoleh gambaran yang lebih jelas. Hasil penelitian ini disimpulkan bahwa GP Ansor adalah organisasi yang memiliki kontribusi besar dalam pergerakan kebangsaan Indonesia. GP Ansor melakukan berbagai upaya di dalam merebut dan mempertahankan kemerdekaan Indonesia. Upaya tersebut dilakukan secara intensif, konsisten dan berkesinambungan sebagai bukti nyata kontribusi GP Ansor dalam menjalankan misi kebangsaannya.